Aluminium diboride‐type structure in Ethiopian opal‐CT revealed by fast Fourier transform. Issue 1 (14th December 2017) - Gauthier, J.-P.; Stephant, N.; Rondeau, B.; Cody, J. A.; Fritsch, E.
Abstract : The structure of a natural CT opal from Ethiopia is explored with a new method, using Fourier transformation, applied to scanning electron microscope images. Abstract : Invisible on a scanning electron microscope image of the surface of an Ethiopian opal rough fracture, a periodic arrangement was detected by fast Fourier transform. Using a mask to eliminate the continuous background and keeping only the bright spots in the reciprocal space (fast Fourier transform pattern), an image reconstructed by inverse fast Fourier transform (IFFT) emphasizes a very regular bidisperse array. Taken on a vicinal plane, the image of the successive steps of the stacking allows identification of the crystallographic structure and estimation of the parameters of this aluminium diboride‐type photonic crystal. In addition, another more complex IFFT image allowed confirmation of the structure and determination of the crystallographic indexing of the steps, despite image deformation due to the tilt of the vicinal plane under the electron beam.